How do you solve 3u + z = 15 and u + 2z = 10?
1 Answer
Sep 7, 2015
Explanation:
Your system of equations looks like this
{(3u+z = 15), (u + 2z = 10):}
Multiply the first equation by
{(3u+z = 15 | * (-2)), (u + 2z = 10):}
{(-6u-2z = -30), (u + 2z = 10):}
Add these two equations to get one equation with one unknown,
-6u - color(red)(cancel(color(black)(2z))) + u + color(red)(cancel(color(black)(2z))) = -30 + 10
-5u = -20 implies u = ((-20))/((-5)) = color(green)(4)
Now use this value of
4 + 2z = 10
2x = 6 implies z = 6/2 = color(green)(3)